Tourism and the Value System: An Impact Assessment from Socio-cultural Perspective - Sharma, Ramji (Himalayan Journal of Sociology and Anthropology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> The contemporary world has given a high priority to the development of tourism for the reason that it is considered as an export business without actually sending any tangible products out of the boarder. Beside its economic gain, its effects and implications appear in myriad of forms and guises both in pros and cons. Some of them are latent just performing as instigating agents while some are manifest functioning proactively; some are momentary and some are enduring too. From socio-cultural dimension, tourism appears as a powerful agent of diffusion, acculturation and assimilation. It influences, directly or indirectly, each and every aspects of the host society. The value system of the tourist receiving community can not remain in isolation. This study covers the impacts caused by the development of tourism business over the selected components of the value system of host societies viz. Lakeside of Pokhara and Sarangkot of Kaski. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1499 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.106-125